Hijrah Intention And Type Of Customer Loyalty of Islamic Banks In Indonesia - Fetria Eka Yudiana; Hadri Kusuma; Ibnu Qiyam (Ekonomi Syariah IAIN Kudus, 2021)
The purpose of this research is to investigate the influence of hijrah intention on customer loyalty in Islamic banks including the type of loyalty based on attitude and behavior. In this research, Islamic banks customers in Indonesia were used as the population, and 360 questionnaires were distributed using the convenience sampling technique. The research hypothesis was tested using Structural Equation Model (SEM) with PLS. All the indicators for the variables of interest were reflective and adapted from some previous literature. The data in this research met the requirements for convergent and discriminant validity and the results showed that hijrah intention had a direct effect on attitude and behavioral loyalty. Furthermore, the hijrah intention provides a stronger influence for attitude loyalty than behavioral loyalty. The results of this research show that the majority of Islamic bank customers were classified as latent loyal.